Design, synthesis, characterization, in vitro screening, molecular docking, 3D-QSAR, and ADME-Tox investigations of novel pyrazole derivatives as antimicrobial agents. (20th January 2022) - Chalkha, Mohammed; Akhazzane, Mohamed; Moussaid, Fatima Zahrae; Daoui, Ossama; Nakkabi, Asmae; Bakhouch, Mohamed; Chtita, Samir; Elkhattabi, Souad; Housseini, Abdelilah Iraqi; El Yazidi, Mohamed
Abstract : Novel pyrazoles were synthesized and evaluated for their antimicrobial activity. Molecular docking, 3D-QSAR, drug-likeness property and ADME-Tox studies were performed. Abstract : In this work, we report the synthesis of some new pyrazole derivatives via an efficient and practical procedure. The structures of the obtained compounds were established using different spectroscopic techniques such as NMR and FT-IR spectroscopy as well as high resolution mass spectrometry (HRMS). The synthesized compounds were screened for their antimicrobial activity against the following pathogenic microorganisms: Listeria innocua (CECT 4030), Staphylococcus aureus (CECT 976), Escherichia coli (K12), and Candida albicans (ATCC 10231). The results of the in vitro tests reveal that compounds 5c, 9b, and 9c exhibit important antimicrobial activity against some tested microbe strains, and show excellent bactericidal and fungicidal activities. A molecular docking study was performed on the most active compounds against E. coli and C. albicans receptors, in order to determine the modes of hydrogen bonding, and electrostatic and hydrophobic interactions that occur between the selected ligands and the target proteins. Furthermore, the 3D-QSAR study based on CoMFA and CoMSIA analyses ascertained a good correlation between the antibacterial activity of the pyrazole derivatives and their structural parameters. The structural features identified in these analyses were successfully used to design new pyrazole derivatives that show better in silico antimicrobial activity than the synthesized ones. In addition, most of the synthesized and the newly designed compounds show good drug-like properties. The ADME-Tox profiles indicate a good oral bioavailability. The newly designed compounds were subjected to molecular docking, which showed that they could form stable complexes with the E. coli receptor. Therefore, the obtained results in this study might provide important information for designing and synthesizing new pyrazoles with enhanced antimicrobial activity.